Annual Review of the Sociology of Religion. Volume 16 (2025) : From Cases to Scandals: Sexual Abuse in the Catholic Church - Béraud, Céline,; Giordan, Giuseppe, (Annual Review of the Sociology of Religion ;, 2026)
The volume "From Cases to Scandals: Sexual Abuse in the Catholic Church" contributes to the sociology of religion by examining how individual cases of clerical sexual abuse escalate (or not) into scandals that challenge religious authority and reshape institutional life. It explores how the strategies of public mobilisation and media responses encourage collective reflection and action to ensure accountability and societal change. Through case studies from Argentina, Canada, Croatia, Czechia, France, Italy, Germany, Poland, Spain, the Netherlands, and the U.S., this volume explores Church responses, believers' reactions, and the shifting dynamics of trust and legitimacy. It highlights how these developments affect religious affiliation, moral credibility, and the public role of the Church, offering new perspectives on the evolving relationship between religion, society, and scandal in contemporary contexts.